Novo modelo de indução de tendinite equina: avaliação clínica e ultrassonográfica - Carvalho, Armando de Mattos; Yamada, Ana Lucia Miluzzi [UNESP]; Álvarez, Luis Emiliano Cisneros; Jorge, Luciana Leal; Conceição, Mariana Lopes da [UNESP]; Mattos, Luiz Henrique; Hussni, Carlos Alberto [UNESP]; Alves, Ana Liz Garcia [UNESP] (GN1 Sistemas e Publicacoes, 2015)
The objective of this study was to evaluate clinically and ultrasonography a tendinitis new induction methodology of superficial digital flexor tendon (SDFT) in horses. Eight adult horses clinically healthy were used. The injury induction was performed with a collagenase suspension in gel, which was administered at the central SDFT medium with the use of ultrasound. The animals were followed for 15 days post-induction, where physical and ultrasound examinations were performed. Lameness was also evidenced in all animals and SFDT lesion could be confirmed by ultrasound analysis. The technique adopted for the experimental induction of tendinitis in horses proved to be effective and may be used to improve the implementation of new studies involving the treatment of experimentally induced tendinitis.

O objetivo deste estudo foi realizar a avaliação clínica e ultrassonográfica de uma metodologia de indução de tendinite do tendão flexor digital superficial (TFDS) em equinos. Foram utilizados oito equinos adultos, hígidos submetidos a indução de uma lesão realizada com suspensão de colagenase em gel, que foi administrada na região central média do TFDS com o auxílio do aparelho de ultrassom. Os animais foram acompanhados durante 15 dias pós-indução, onde foram realizados exames clínicos e ultrassonográficos. Foi evidenciada claudicação em todos os animais. Na avaliação ultrassonográfica pode ser confirmada a tendinite do TFDS. A técnica adotada para a indução experimental da tendinite em equinos demonstrou ser efetiva e poderá ser utilizada para aperfeiçoar a execução de novos estudos envolvendo o tratamento de tendinites experimentais induzidas.
New model of equine tendinitis induction: clinical and ultrasound evaluation
Keywords: Collagenase; Gel; Lesion; Tendon; Colagenase; Gel; Lesão; Tendão